2013
DOI: 10.1007/978-3-319-01848-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning Organ Allocation Boundaries for Liver Transplantation in the United States

Abstract: Geographic disparities in access to and outcomes in transplantation have been a persistent problem widely discussed by transplant researchers and the transplant community. One of the alleged causes of disparities in the United States is administratively determined organ allocation boundaries that limit organ sharing across regions. This paper applies mathematical programming to construct alternative liver allocation boundaries that achieve more geographic equity in access to transplants than the current system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The difference between the minimum and maximum values in Table 4 were significant, which indicates that there are regions where the OPO supply/demand was close to 1 and others were the ratio was close to 0 (no supply), which amounts to severe geographical disparity. The average value of the supply/demand ratio was 0.46, which is close to the US national average for supply/demand (Koizumi et al 2014b).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The difference between the minimum and maximum values in Table 4 were significant, which indicates that there are regions where the OPO supply/demand was close to 1 and others were the ratio was close to 0 (no supply), which amounts to severe geographical disparity. The average value of the supply/demand ratio was 0.46, which is close to the US national average for supply/demand (Koizumi et al 2014b).…”
Section: Discussionsupporting
confidence: 62%
“…Some these studies that redrew the OPO and UNOS boundaries without adding new transplant centers include the work by Gentry (2013) and Demicri (2012), all of which have attempted to balance efficiency and equity of allocation. Another research studied by Koizumi et al (2014aKoizumi et al ( , 2014b) performs a location allocation analysis that determines new locations of liver transplant centers, and converts some of the kidney transplant centers into both kidney and liver transplant centers, which have partially alleviated geographical disparity but adds to the infrastructure costs of expanding the number of TX in the USA. It is generally believed that, in reality, changing administration and jurisdiction by redrawing UNOS and OPO boundaries cannot be easily implemented due to the physical infrastructure costs, political and state issues and mandates, new staffing and training requirements, and equity issues from new boundaries that affect the allocation of livers for already registered candidates.…”
Section: Related Literaturementioning
confidence: 99%
“…Discrete event simulations (DES) can represent the competition for resources and investigate the changes in stochastic systems[ 26 , 27 ], and are mainly used to evaluate health care systems. The capacity and utility of allocation systems have previously been assessed before and after policy changes[ 28 - 31 ]. Another example reported by Shechter et al[ 26 ] is a biologically-based discrete-event simulation model, which represents the biological progression of end stage liver disease (ESLD) and examines the impact of changing allocation policies on this issue.…”
Section: What Is Decision Modelling?mentioning
confidence: 99%
“…The current boundary based allocation system gives rise to several issues such as geographical disparity in access, long system waiting times, possible liver wastages due to long transportation time, and giving access to a candidate lower in the priority list than the neediest candidate. By applying simulation optimization, Koizumi et al (2013Koizumi et al ( , 2014 and Feng et al (2013) have demonstrated the effectiveness of mitigating those issues and offering better allocation.…”
Section: Using Simulation Optimization To Manage Liver Transplantmentioning
confidence: 99%